Quantificação e efluxo de colesterol total e HDL dos espermatozóides do ejaculado de caprinos - Vilar, Emanuel Limaverde (2010)
The objective was to measure the rate of cholesterol present in seminal plasma (SP) goats, and verify whether cholesterol efflux from sperm to the PS, and as such event occurs individually after one hour incubation at 38 ° C. The experiment was conducted at the Laboratory for Animal Reproduction, UFC. Eight goats were used intensively reared and fed according to NRC / goat (1981). The ejaculates collected were divided into three aliquots. The was first centrifuged to obtain the PS, which was packed in tubes eppendorfs and stored at -18 ° C. The second aliquot was incubated at 38 ° C / 1 h and then centrifuged to obtain the PS. These two samples were analyzed the level of total cholesterol and HDL. The third aliquot was diluted in sodium citrate - glucose and subjected to heat resistance test for evaluation of force, mobility, normal sperm cells and morphological changes in total. The design trial was a randomized block design to data analysis was used The statistical program SAS @ 9.0. There were significant reductions of force and motility between incubation times. However, in most animals parameter stabilization occurred after 60 min of incubation. Small difference was observed among individuals for these parameters. Cholesterol Total found in PS of goats increased significantly after incubation in 50% of animals. Before and after incubation, the level of total and HDL cholesterols ranged significantly among individuals. The proportion of HDL cholesterol in the ER was very high values ​​were 83.79% and 78.41% respectively. We observed a association (p <0.01) positive and moderate between the proportion of HDL and sperm vigor (r = 0.30) and between the motility and the proportion of HDL was considered small (r = 0.19). It was concluded that PS goats contains a high proportion of cholesterol and cholesterol This is the main HDL.